Knowledge, attitudes, and practices of adolescent depression among parents of children diagnosed with depression in Ningbo City, eastern China - Gao, He; Dai, Ni; Lin, Chen; Ye, Yun; Yang, Dalu; Zhang, Qingyu; Mao, Jiaxin; Lou, Zhongze; Ji, Yunxin; Ruan, Liemin; Hou, Yanbin (Frontiers in Public Health, 2024)
Objective: To investigate parental knowledge, attitudes, and practices (KAP) toward adolescent depression. Methods: A cross-sectional survey was conducted between October 2022 and October 2023 at The First Affiliated Hospital of Ningbo University among parents of adolescents diagnosed with depression. A self-administered questionnaire was used to collect the parents’ demographic characteristics and KAP towards adolescent depression. Results: A total of 522 questionnaires were collected from parents of depressed adolescents. Among the participants, 383 (73.37%) were female. In addition, 426 participants (81.61%) had children aged 14 - 18. The mean knowledge, attitude, and practice scores were 9.09 ± 2.37 (possible range: 0 - 12), 37.04 ± 4.11 (possible range: 11 - 55), and 31.53 ± 3.84 (possible range: 8 - 40), respectively. There were significant positive correlations between knowledge and attitude (r = 0.225, P < 0.001), knowledge and practice (r = 0.240, P < 0.001), and attitude and practice (r = 0.381, P < 0.001). The path analysis showed significant direct effects of knowledge on attitude (β = 0.422, P < 0.001) and practice (β = 0.283, P < 0.001). There was an indirect effect of knowledge on practice through attitude (β = 0.131, P = 0.004). Attitude directly impacted practice (β = 0.311, P < 0.001). Conclusion: Parents of adolescents diagnosed with depression exhibited moderate KAP regarding adolescent depression. The study underscored the importance of targeted interventions to improve parental KAP in supporting adolescents with depression. Moreover, future research should explore additional factors influencing parental attitudes and behaviors toward adolescent depression to develop more effective interventions.